ALEXANDER MEZHIROV IN THE DIARY ENTRIES OF LEVON MKRTCHYAN - SAHAKYANC, KARINE (Bulletin of Yerevan University H: Russian Philology, 2019)
The paper follows a number of articles, published earlier in “The Bulletin of Yerevan University. Russian Philology” under the single title “From the Archives of Levon Mkrtchyan”. The archive of literary critic, professor of the Yerevan State University specialized in translation studies, academician of the National Academy of Sciences of Armenia L. Mkrtchyan (1933-2001) preserves numerous texts and documents which, in particular, highlight L. Mkrtchyan’s literary contacts, remarkable for the examination of Armenian-Russian literary-cultural links from the second half of the XX century. The presented diary entries testify the nature and contents of his long communication with the famous Russian poet and poetry translator Alexander Mezhirov (1923-2009), including the latter’s high interest towards “The Book of Lamentations” by Narekatsi.
Keywords: Levon Mkrtchyan, Mezhirov, contacts, archive, diary, poetry, translation, Narekatsi